A pilot study of 4CYTE™ Epiitalis® Forte, a novel nutraceutical, in the management of naturally occurring osteoarthritis in dogs. Issue 12 (26th September 2020) - Beths, T; Munn, R; Bauquier, SH; Mitchell, P; Whittem, T
Abstract : The primary goal of this pilot study was to assess, the efficacy of a new nutraceutical, 4CYTE™ Epiitalis® Forte, containing, as a standalone, a proprietary plant oil extract, Epiitalis, in dogs presenting with signs of osteoarthritis (OA). Fifty dogs aged 9.2 (±3.2) years with signs of naturally occurring OA were included in this report. They were free of other comorbidities and were not on any medications except for those utilised for managing their OA. In these dogs, the current treatments were continued to avoid any sudden changes in their disease management. The effects of the 4CYTE Epiitalis Forte were assessed both at the beginning and at the end of a 1 month‐long treatment period. The evaluation consisted of an objective lameness assessment (TPI%[total pressure index]) using a gait analysis (GAITRite® Portable Walkway System) and a subjective quality‐of‐life questionnaire, the Helsinki Chronic Pain Index (HCPI). Additional exploratory objective measurements included the Symmetry Index (SI) and the fore/hind limb ratio (T/P TPI%). Of dogs, 74% (34/46) registered a numerical improvement in TPI% in their worse limb. In addition, of the 93.5% of the dogs that demonstrated improvement in their HCPI scores by at least 5% on the quality‐of‐life questionnaire, 79% demonstrated improvements in gait based on TPI%. Finally, there were improvements measured in both exploratory objective endpoints SI and T/P TPI%. These encouraging results will be used to develop a protocol for a follow‐up placebo‐controlled randomised study to confirm the efficacy of this new nutraceutical for dogs suffering from OA.